Understanding the importance of parent learning in a school-based family literacy programme. (December 2015) - Timmons, Kristy; Pelletier, Janette
This study examined how parents' own learning affected their support for their children in a school-based Family Literacy Programme. Seventy-two children in junior kindergarten (4-year-olds) and senior kindergarten (5-year-olds) and their parents participated in the programme; complete data were available for 52 parents. Comparisons of pre- and post-programme parent surveys indicated that there was no significant difference in how parents viewed their role in affecting their child's reading as a result of the programme. However, parents' teaching behaviour and provision of literacy activity (library visits) with their children significantly increased as a result of the programme. Furthermore, parents' reported level of enjoyment of literacy activities with their children increased significantly in the areas of reading, drawing and writing. Finally, parents' goals for attending the programme were aligned with what they described learning from the programme. The results suggest that family literacy programmes help parents to gain literacy knowledge and skills that they then incorporate in daily interactions with their children, particularly when programme objectives match parents' goals. The findings suggest that parents may benefit from longer programmes to provide them with additional learning strategies for engaging in literacy activities with their children.